The influence of red light on the growth and carbohydrate content in short-day and neutral lines of soybean - Тимошенко, В. Ф.; Жмурко, В. В. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 2013)
The influence of red light (660 nm) on growth, content of different forms of carbohydrates and amylase activity in short-day and neutral isogenic lines of soybean (Glycine max. L. (Merr.)) have been investigated in vegetative experiments. It has been found that activation of phytochromes by red light in the short-day soybean line causes decrease in the content of reducing sugars and starch, but increase of water-soluble carbohydrates, plant height and biomass. It is suggested that red light stimulates utilization of carbohydrates in growth processes in short-day line of soybean. The effect of red light on the investigated parameters in neutral soybean line has not been identified.